An exploration of the perceptions of and risk and protective factors for drug use among young persons aged between 18 and 24 years in Mufakose, Harare, Zimbabwe - Chivese, Nyamadzawo (Centre for Public Mental Health, 2018)
Background: Drug use by young people is on the increase globally, regionally and locally, in Zimbabwe. Most of what is known about the risk and protective factors for drug use has been written from studies done in high income countries. Limited studies focused on the low to medium income countries. The available literature for Zimbabwe is a few quantitative studies, done nearly two decades ago. These might not still be relevant today because of the generational changes that have taken place in the society over time. Methods: A qualitative study was conducted in Mufakose, one of the low income high density suburbs of Harare, Zimbabwe. The aim of the study was to find out the reasons why young people in the community were using drugs while others within the same geographical area were not using. A purposive sampling method was used to recruit 40 young people aged between 18 and 24 years who were current drug users, past users and those who had never used drugs at all in their entire lifetime. Individual in-depth interviews and focus group discussions were conducted at two community centres in the community to elicit data from the participants. Data collected from the in-depth interviews and focus group discussions were analysed using NVivo using themes that were derived from literature. Results: Results showed that both risk and protective factors for drug use exist at three levels of human interaction: the micro, meso and macro levels. Micro level risk factors included stressors from the home or living arrangements or workplace, stress due to loss of a loved one, boredom due to unemployment and lack of activities, a lack of commitment to work, sport or school and one's beliefs. Meso level risk factors were exposure to the drug using behaviour by peers and bullying. At family level, exposure to drug use, family conflicts were reported as risk factors. At macro level, drug availability and cost and media influence were cited as risk factors for drug use among the group. For the protective factors leading to non-use, religion was the strongest protective factor at all the three levels. A commitment to work, sport or school was also protective at micro level. Non-exposure to drug using behaviour were protective at the meso level. Conclusion: The current social environment in Zimbabwe together with a breakdown of the country's institutions such as marriage due to death, divorce or migration to other countries. The breakdown has left some children in single parent families vulnerable to a life of drug use. Early initiation into drug use was reported to be through exposure from peers, families and other members of the community as young people in Mufakose are using drugs in-order to escape from the reality of life. Evidence based psychosocial interventions could be used to reduce the impact of drug use among this population.